ANTECEDENTS AND CONSEQUENCES OF CUSTOMER EXPERIENCE IN SKINCARE PRODUCTS - John David Daniel Hutasoit; Kurniawati Kurniawati; Yolanda Masnita (Journal of Management Small and Medium Enterprises (SME's))
This study aims to identify and measure the extent to which employee empathy, communication with staff, and transaction convenience influence the formation of brand love and brand loyalty. The unit of analysis for this research is the users or consumers of skincare products. The research method applied in this study is quantitative. Data were collected through questionnaires distributed to users of skincare products from various brands. The results indicate a positive impact of transaction convenience on customer experience, a positive effect of customer experience on brand love, and a positive influence of brand love on brand loyalty. Managers should focus on staff openness, expectation management, inventory, and improvement processes, as well as product return processes, expectation adjustments, and loyalty programs.